The Effectiveness of the Islamic Input in Medical Practice (IIMP) in Improving the Knowledge, Attitude and Practice among Medical Students in Malaysia. A 5-year Prospective Study - Musa, Ramli; Khoiriyah, Umatul; Mohd Arifin, Siti Roshaidai; Dzulkarnain, Ahmad Aidil Arafat (IIUM Medical Journal Malaysia, 2022)
Introduction; In order to produce well-rounded medical doctors in the future, Islamic-based Medical schools in Malaysia and other parts of the world are implementing a special approach in their curricula. The main vision of these medical schools is instillation of Islamic values in their curricula. In International Islamic University of Malaysia (IIUM), a special curriculum namely Islamic Input in Medical Practice (IIMP) was introduced for this purpose. The importance of this study is to measure the effectiveness of this program on the aspects of knowledge, attitude and practice among our students. Materials & Methods: We follow up a total of 142 students for 5 years duration. The first assessment was done right at the enrolment to the medical program and the second assessment by using the similar questionnaire was done after 5 years upon completion of their course. Results: From a total number of students 145 from initial assessment, only a total of 102 medical students completed second time. The remaining number were excluded due to either incomplete forms and delay the academic progress due to failure of subjects. The mean different between pre and post shows a significant improvement in all 3 measured aspects (p<0.001 to 0.022). Conclusion: The 5-year evidence shows our IIUM program is effective to improve the knowledge, attitude and practice.